(untitled) (Annual of the Faculty of Philosophy in Skopje, 2021)
The amalgamation of the two traditions of thought, the Aristotelian and the Christian, in the ethics of St. Thomas Aquinas was also reflected in the development of the concept prudentia. Prudentia in Aquinas’ philosophy is directly modeled on Aristotle’s φρόνησις, but converges in the theological characteristics that he attributes to this concept: the relation of prudentia and the theological virtues given by God’s grace, the relation between prudentia and divine providentia, the relation of prudentia with charity, and the most significant characteristics - the introduction of natural law and synderesis - the innate human ability to recognize the eternal first principles of moral reasoning. This article follows through the main aspects of this concept in the philosophy of St. Thomas Aquinas and problematizes the novelties he introduces. The main component that allows Aquinas to overcome the great problems that arise in defining prudentia is the addition of natural law. With this intervention by Aquinas, the flexibility of Aristotle’s ethics has been replaced by more certain principles that determine moral actions. But the question remains how valuable it is to sacrifice freedom at the expense of certainty in moral deliberation and action.